MEMBRANE SCRAPER MADE BY POLYPROPYLENE LOOP: An Instant Intraoperative Solution for the Induction of Posterior Vitreous Detachment. Issue 12 (December 2021) - Jiang, Feng; Zhang, Wen-wen; Liu, Ya-jun; Chen, Fei-fei; Xie, Zheng-gao
Abstract : Supplemental Digital Content is Available in the Text.